Changes in Growth and Muscle Quality of Largemouth Bass (Micropterus salmoides) Reared in Recirculating Aquaculture System - ZHOU Xiuzhen, ZHANG Yi, ZHOU Qin, DING Xueyan, LI Ming, JIA Jia, HUANG Ju, WANG Yang (Shipin Kexue, 2024)
In order to investigate the effect of a recirculating aquaculture system on the body indexes, texture, nutrient composition and earthy odor substances of largemouth bass (Micropterus salmoides), this study determined texture characteristics of fish meat such as hardness, springiness and chewiness, and used conventional biochemical methods, an amino acid automatic analyzer, and gas chromatography (GC) to detect the contents of moisture, ash, crude protein, crude fat, fatty acids, and amino acids. Meanwhile, gas chromatography-mass spectrometry (GC-MS) and electronic tongue were used to analyze the earthy odor substances and taste of fish meat. The results showed that the ratio of liver to body mass decreased significantly with rearing time; after rearing for up to 20 days, the hardness, cohesiveness, chewiness, springiness, adhesiveness and gumminess of fish meat were improved compared with those before rearing. The crude fat content initially increased and then decreased with rearing time, while the moisture content showed an opposite trend. The contents of protein, ash, flavor amino acids, essential amino acids, and monounsaturated fatty acids in fish meat increased after 15 days of rearing. The contents of sum of eicosapentaenoic acid methyl ester, docosahexaenoic acid methyl ester and ω-3 fatty acids significantly increased after 5 and 15 days. In addition, the contents of water-soluble protein and non-protein nitrogen in fish meat also increased significantly; with increasing rearing time, fish meat showed an increase in flavor differences, and the content of earthy odor substances decreased, which was below the sensory threshold from day 15 onward. Taking into account the body indexes, nutrient composition and earthy odor substances of largemouth bass muscle, a rearing period of 15 days in the recirculating water system is recommended.